Analisis Pengembangan Model Bisnis pada Perusahaan Jasa K3 Menggunakan Business Model Canvas (Studi Kasus Pada PT. ABC) - Andi Balladho Aspat Colle; Kholil; Soehatman Ramli (Syntax Corporation, 2022)
This research aims to develop an appropriate business strategy based on Business Model Canvas (BMC) during COVID-19. It was a strategic management research design carried out at PT. ABC. Data analysis was carried out by (1) Identification of the BMC, (2) Identification of strategic issues of internal and external factors from 9 elements of BMC, (3) Formulation of Strategy through 3 stages, namely the input stage (Internal Factor Evaluation (IFE) Matrix and External Factor Evaluation (EFE) Matrix), matching stage (Internal External (IE) Matrix and SWOT Matrix) and decision stage. The study results showed several points on the BMC elements of PT. ABC needs to be updated, so it is right on target, including (a) Customer Segments: adding students and graduate students. (b) Value Proposition: Additional income for non-alumni (employees, students, and fresh graduates) and adequate information related to occupational health and safety (c) Channels: adding Search Engine Optimization (SEO) to improve the communication system and include non-inhouse sales. (d) Customer relationships: using Telegram as social media, (e) Key Activities: marketing activities carried out by marketing staff from home. (g) Key Partnership: involving freelance marketing as main partner. Then, using Google, LLC, into a key partnership. (g) Cost Structure: includes marketing fees for freelance marketing.